2019
DOI: 10.1039/c9cp00539k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton uptake on the structure of energy levels in the band-gap of Sr-doped LaScO3: diffuse reflectance spectroscopy and coherent potential approximation calculations

Abstract: The obtained results explain features of LaScO3 optical properties and the effect of acceptor doping and H2 and H2O uptake on them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…A number of experiments revealed strong optical absorption in La 1− x Sr x ScO 3− δ at an energy of about 0.5–1 eV below the fundamental absorption edge. 63,64,72 Similar levels have been found in X-ray absorption spectroscopy studies. 73,74 Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A number of experiments revealed strong optical absorption in La 1− x Sr x ScO 3− δ at an energy of about 0.5–1 eV below the fundamental absorption edge. 63,64,72 Similar levels have been found in X-ray absorption spectroscopy studies. 73,74 Fig.…”
Section: Resultssupporting
confidence: 84%
“…LaScO 3 is an insulator with a band gap of about 6 eV. [63][64][65] The valence band consists predominantly of the O2p states, while the conduction band consists of the d states of La and Sc. Acceptor doping, in accordance with eqn (1), creates two types of defects: a dopant atom in the position of La and an oxygen vacancy, the concentration of which is much higher than the concentration of defects of another type.…”
Section: Electronic Structurementioning
confidence: 99%
“…It has been reported that, in the absorption spectrum of proton conductors obtained from powder and single crystal specimen, weak optical absorption associated with the defect levels can be observed in the lower photon energy region below the fundamental absorption edge for the samples annealed in dry conditions. 18,20 In contrast, the weak absorption which is sensitive to the annealing condition was not observed in the spectra of our thinfilm specimen and the absorption spectra mostly coincided with each other in spite of the difference in the annealing condition for both the BZY/SiO 2 and the SZY/SiO 2 . The absence of the apparent dependence of the absorption spectrum on the annealing condition indicated that the observed strong absorption was the fundamental absorption arising from the photoexcitation of electron from the VB to the CB.…”
Section: Optical Propertiesmentioning
confidence: 48%
“…While first-principles calculations based on the density-functional theory (DFT) have been widely used to uncover the mechanisms of proton migration and a proton-trapping effect by acceptors doped in the protonconducting oxides, [13][14][15][16][17] some researchers have investigated the interactions between protons and acceptors by experimental electronic structural analyses based on optical absorption measurements. [18][19][20][21] Sata et al, reported that, in Y and Sc-doped SrZrO 3 (SZO) single crystals, characteristic defect-related optical absorption derived from electron transition from the acceptor levels to the conduction band minimum (CBM) can be observed for the crystals annealed under dry air, whereas the defect-related absorption is weakened after annealing in humidified air. 18 The weakening of the defect-related absorption is an indication of the interaction between the acceptors and protons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation